The Mental Health Implications of Acne Vulgaris - Sieradocha, Kamila (Quality in Sport, 2024)
Acne vulgaris, a prevalent chronic inflammatory skin condition, affects approximately 9.4% of the global population, with implications that extend beyond physical appearance to significantly impact mental health. While acne primarily manifests through visible skin lesions, such as comedones, papules, and pustules, the condition’s psychological toll can be profound. Many individuals with acne experience elevated levels of anxiety, depression, and reduced self-esteem, especially adolescents, for whom acne can disrupt self-identity formation. These mental health challenges are often exacerbated by the social stigma associated with visible skin conditions, leading to issues like social withdrawal, body image concerns, and, in severe cases, even suicidal thoughts. Effectively managing acne requires a holistic approach that addresses both physical symptoms and psychological well-being. Dermatological treatments, including topical retinoids, benzoyl peroxide, and oral isotretinoin, are commonly used to control acne symptoms. Dietary modifications, such as reducing high-glycemic foods and dairy, and the use of probiotics, have shown promise as supportive measures. However, addressing the psychological component is equally critical; integrating psychological interventions, such as counseling, cognitive-behavioral therapy, and patient education, can help alleviate the mental strain associated with acne, improve adherence to treatment, and enhance quality of life. Further research is essential to explore the long-term benefits of combined dermatological and psychological treatments and to develop personalized approaches that consider individual psychological profiles. A comprehensive treatment model that incorporates both physical and mental health support offers the potential for improved outcomes, fostering both dermatological recovery and mental resilience in individuals affected by acne vulgaris.